2015
DOI: 10.1001/jama.2015.459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Eliglustat on Splenomegaly in Patients With Gaucher Disease Type 1

Abstract: IMPORTANCE Gaucher disease type 1 is characterized by hepatosplenomegaly, anemia, thrombocytopenia, and skeletal disease. A safe, effective oral therapy is needed.OBJECTIVE To determine whether eliglustat, a novel oral substrate reduction therapy, safely reverses clinical manifestations in untreated adults with Gaucher disease type 1. DESIGN, SETTING, AND PARTICIPANTS Phase 3, randomized, double-blind, placebo-controlled trial conducted at 18 sites in 12 countries from November 2009 to July 2012 among eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 22 publications
(28 reference statements)
4
126
0
5
Order By: Relevance
“…We focused on the same drug target as for Gaucher disease (that is, glucosylceramide synthase), as antagonism of this enzyme with eliglustat (Genz-112638) has been shown to be safe and effective in human studies (37,38). Eliglustat was recently approved in the United States and the European Union as a firstline oral therapy in adult patients with Gaucher disease type 1 who are poor, intermediate, or extensive CYP2D6 metabolizers.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the same drug target as for Gaucher disease (that is, glucosylceramide synthase), as antagonism of this enzyme with eliglustat (Genz-112638) has been shown to be safe and effective in human studies (37,38). Eliglustat was recently approved in the United States and the European Union as a firstline oral therapy in adult patients with Gaucher disease type 1 who are poor, intermediate, or extensive CYP2D6 metabolizers.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Eliglustat acts by partially inhibiting the de novo biosynthesis of b-glucosylceramide, thereby rebalancing the rate of formation of the primary substrate of the deficient enzyme with its impaired degradation. In clinical phase 2 and 3 studies of previously untreated patients with Gaucher disease type 1, eliglustat induced clinically meaningful improvements in hematological parameters as well as spleen and liver volumes at 9 to 12 months, 8,9 which were maintained at 18 months 10 and after 4 years. 11 Bone mineralization density also continued to improve after 1 to 4 years of eliglustat.…”
Section: Introductionmentioning
confidence: 95%
“…61 In our review of studies including Latin American patients undergoing intervention for Gaucher disease, we summarized the studies that had two time points at which patients underwent an intervention, and examined the outcome on skeletal manifestations. These studies 29,30,33,[62][63][64][65][66] showed similar outcomes to the international literature and consensus 59 providing evidence that treatment, especially early intervention, improves skeletal outcomes. (Table 2) …”
Section: Management/treatmentmentioning
confidence: 60%